PERAN GURU BIMBINGAN KONSELING DALAM PERENCANAAN KARIR SISWA MELALUI BIMBINGAN KELOMPOK DENGAN MEDIA POHON CITA-CITA - Elida Hapni; Silvianetri Silvianetri (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
The aim of this research is to find out the role of guidance and counseling teachers in planning students' careers through group guidance using the dream tree as a medium. This type of research is qualitative descriptive in the form of words and actions of individuals who are used as informants in this research. The informants for this research were three guidance and counseling teachers, while the research instruments were the researchers themselves using interview and observation techniques. After the data is obtained, data analysis is carried out without stopping until the data is saturated. Data reduction, data presentation, and drawing conclusions are the three stages of the data analysis process. Triangulation techniques are used to verify the validity of the data, which includes: source triangulation, technical triangulation, and time triangulation. The research results show that the efforts made by guidance and counseling teachers go through several stages, namely: planning, implementation, evaluation of results, and follow-up. Furthermore, guidance and counseling teachers also experience implementation problems, including: the limited time given for guidance in class, namely only one lesson hour (or forty minutes). This also occurs when there are no subject teachers in the class. So that students feel that the time is too short and the activity material has not reached the goal in accordance with the service implementation plan.